Identification of Morphological and Growth Characteristics of Eisenia foetida in Mushroom Media Waste - Ana Mardiana; Baiq Mirawati; Hunaepi Hunaepi; Desi Ratnasari; Hilda Aqua Kusuma Wardhani; Ahmad Aris Arifin (School of Postgraduate Studies, Diponegoro Univer, 2025)
This study aims to determine the morphological and growth characteristics of Eisenia foetida in response to mushroom waste media. Two types of mushroom waste media were used: straw mushroom media waste and oyster mushroom baglog waste. The research design was experimental, using quantitative methods and descriptive statistical analysis. The study observed parameters such as body length, body weight, skin color, population, and biomass of Eisenia foetida. The results showed significant differences in the growth and morphological characteristics of Eisenia foetida among the various media treatments. The oyster mushroom waste media with higher composition (80%) yielded better growth in terms of body weight and biomass compared to the straw mushroom waste media. Specifically, the treatment with 80% oyster mushroom waste and 20% straw mushroom waste (P3) showed the highest average body weight (17.13 g). In conclusion, mushroom media waste, especially oyster mushroom baglog waste, supports the optimal morphological development and growth of Eisenia foetida. These findings suggest that oyster mushroom waste can be effectively utilized as a medium for cultivating Eisenia foetida, providing an environmentally friendly solution to organic waste management. Recommendations for future research include exploring other types of organic waste as potential media for Eisenia foetida cultivation and conducting long-term studies to evaluate the sustainability of such media.